Introdução à Tropicologia: A Problemática Ecológico-Geográfica (I) - Andrade, Gilberto Osório de (Ciência & Trópico, 2011)
RESUMO A biografia como ecologia do homem. Diferentes sentidos da palavra ecologia. A ecologia natural e suas vinculações com a biogeocenose e com a etologia. ABSTRACT Introduction to the tropicology: the ecological-geographical problems (I). v. 1, n. 1, p. 85-104, jan./jun. 1973. The biogeography as man’s ecology. The different meanings of the word ecology. The natural ecology and its close alliance with “biogeocenose” and with ethology. RESUMÉ Introduction à la tropicologie: la problématique écologique géographique (I). v. 1, n. 1, p. 85-104, jan./jun. 1973. La biogéography comme écologie de l’homme. Le mot écologie et ses différents sens. L’écologie naturelle et ses relations avec la biogéocenose et l’éthologie.